Revival of “Dollar Diplomacy” As United States Foreign Economic Policy in 2017: Tradeoffs Exchanged to Maintain Trade and Restore Peace Along the Tottering Western Pacific Rim - Jones, David A. (Advances in Social Sciences Research Journal, 2017)
Background, Objective and Goals: From their auspicious meeting at the “Southern” White House, Mar-a-Lago, West Palm Beach, Florida on 5-6 April 2017, U.S. President Donald J. Trump and China’s President Xi Jinping seem to have struck up a friendship accord intended to maintain, hopefully augment, Western trade with China and in the process diffuse burgeoning tensions along the Western Pacific rim caused by aggressive rhetoric and belligerent behavior of Kim Jong-Un, leader of the “Democratic” People’s Republic of Korea [North Korea]. In the process, the United States appears to be recasting its foreign economic policy as a return to “Dollar Diplomacy,” the hallmark of American foreign policy during the William Howard Taft presidency (1909 – 1913), mostly out of favour since then until the present moment. An objective of this paper is to clarify and articulate characteristics of “Principled Dollar Diplomacy” in the 21st century compared with its 20th century counterpart, to identify what will be its objectives and goals, then to assess the viability and sustainability of the same globally but especially along Asia’s Western Pacific rim, connecting to South and West Asia then Europe along the ancient “Silk Road” of Eurasia as an integral part of President Trump’s “Principled Realism” in foreign policy. Methods: Literature reviewed include historiographical documents reflecting both the current state of, and recent changes to, United States foreign economic policy globally, termed “Principled Realism” by President Trump as it interfaces foreign economic policy with foreign security policy, focusing particularly on what appears to be a tottering Western Pacific rim of mainland Asia, fragmented by hostile rhetoric, nuclear threats, China’s unilateral South China Sea domination. Government reports by individual countries and trading partners plus journalistic accounts, together with diplomatic interviews have been reviewed. Attention is directed to changes in trade volume involving trading partners generally, together with trade values of both imports and exports across the first six months of the Donald Trump administration compared to similar periods in administrations of former American presidents from Theodore Roosevelt to Barrack Obama. Presidential rhetoric will be analysed as communicated to three categories of recipients: foreign heads of state or heads of government, United States business leaders, the global general public. Some historical records are included, comparing Chinese maritime belligerence along the Western Pacific rim with similar activities engaged in by Imperial Germany during World War I then by Nazi Germany during World War II, each with disastrous consequences. Expected Results: Ever since the Florida summit meeting between Presidents Trump and Xi, an economic dialogue appears to have emerged that has expanded into diplomatic discussions involving the DPRK, Association of South East Nations (ASEAN) partners trading with both China and the United States, India, Japan, South Korea. Predicated upon President Trump’s self-assessment of his first 100 days in office, together with legitimate expectations of other nations, it should be possible to gauge the direction of “Dollar Diplomacy” across the first and second 100 days to predict the Strengths and Weaknesses of early changes in United States foreign economic policies over the first six months of the Trump Administration. Positive or negative results should be apparent in trade regimes, trade value, trade volume, as well as changes in rhetoric along the Western Pacific rim, and intensity of involvement if the state parties themselves. Stated succinctly, this is China’s chance to stand out and become a leader, potentially the leader, in Asia, and to work hand in hand with the United States and the Western Alliance to maintain continuity of “Pax Americana” for another 70 years or longer, an enduring peace from which, arguably, China has benefitted more than most countries, and stands to benefit much more across eight more decades of the 21st century. Amongst other factors, an expectation is to witness the United States and other Western Allies join with China in funding its “One Belt, One Road” or “OBOR” across Eurasia, because by partnering a rapprochement with DPRK, China and the United States should grow closer, greater and fairer trade should emerge between these two nations, that burgeoning friendship should draw in Japan and other huge trading partners of both. Possible as a successor to the ill-fated Trans-Pacific Partnership will be a sustainable “Pax Pacifica” reflecting core values of the West alongside China’s stated commitment to decreasing poverty in developing countries, providing an enormous opportunity for the Trump and Xi Administrations to cooperate harmoniously. In addition to the Pacific rim as a region, the DPRK could benefit from Sino-American investment inside of its borders, particularly if China and the West could construct international joint ventures (IJVs) in the region with each functioning as a check and a balance on the other.